TLC Profiling of Leaves Extracts of Some Aloe Threatened Species Endemic to Madagascar for Their Antioxidant Activity - Rokiman Letsara; Rigobert Andrianantenaina; Gédéon Ngiala Bongo; Colette Masengo Ashande; Mahendra Ilmi S Matondang; Koto-te-Nyiwa Ngbolua; Baholy Robijaona Rahelivololoniaina (Britain International for Academic Research (BIAR) Publisher, 2020)
The World Health Organization reported that at least 80% of populations rely on traditional medicine and medicinal plants for their primary health care. Due to their phytochemical compounds, the plants of the Aloe genus are reported to have high potential antiCovid-19 (and antioxidant properties. The aim of this study is to evaluate the in vitro antioxidant activity of some Malagasy endangered species of Aloe genus. The ethanolic extract of few Aloe of Madagascar leaf extracts was fractionated by liquid-liquid partition using hexane. In total 18 different fractions from 9 species have been used to determine their antioxidant activity through in vitro model by using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assay. Both hexanic extract and aqueous extract displayed antioxidant activities in four species. The most evident antioxidant activity was expressed by A. helenae.